Estimating the Benefits of Improved Rail Access; Geographical Range and Anticipation Effects - Hans R.A. Koster; Jos N. van Ommeren; Piet Rietveld (Tinbergen Institute, 2010)
In this paper we investigate the effects of new railway stations on house prices using an extensive repeated sales dataset over a period of 13 years. We employ semiparametric panel data techniques allowing for anticipation effects of station openings. We show that a kilometre reduction in distance to the nearest railway station increases property values by about 1.5 - 2 percent. The geographical range of the effect is about 3.5 kilometres. Ignoring anticipation effects in the estimation procedure leads to a large downward bias for short time period datasets. We do not find any significant house price adjustment effects after station openings.
Keywords: R21; R40; R41; R42; 330; House prices; Anticipation effects; Repeated sales; Railway development; Semiparametric; Agglomerationseffekt; Arbeitsnachfrage; Betriebliche Standortwahl; Immobilienpreis; Hedonischer Preisindex; Nichtparametrisches Verfahren; Schätzung; Niederlande